Self-Presenting, Performance, And The Appearance Of Sales Promotion Girls (SPG) In The Car Dealer PT. Toyota Merdeka Motor (TOYOTA) Soreang Bandung District - Suminar, Ratna; Devi Sakuntalawati, Ratna; Haryono, Bagus (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Analysis Study on Self-Presenting, Performance, and Appearance of Sales Promotion Girls (SPG) at Toyota Car Dealer Soreang, Bandung Regency. The objectives of this study are (1) To find out the selfpresenting (stage setting) of Sales Promotion Girls (SPG) at PT Toyota Merdeka Motor Soreang BandungRegency, (2) To find out the performance of Sales Promotion Girls (SPG) at PT Toyota Merdeka MotorSoreang Bandung Regency, (3) To find out the appearance of Sales Promotion Girls (SPG) at PT Toyota Merdeka Motor Soreang Bandung Regency. This research uses a descriptive qualitative method with a purposive sampling technique. The data is collected by conducting observation and document research techniques. The informants used in this study as the main sources are sales promotion girls and as keyinformation namely, the Women Dealer Supervisor of PT Toyota. Data analysis techniques used are Milles and Huberman's interactive model with data collection, data reduction, data presentation, and conclusiondrawing. The research analysis technique uses data triangulation. The results showed that the selfpresenting, performance, and appearance of sales promotion girls as follows (1) Self-presenting / selfpresentation of an SPG namely physical and mental appearance, polite and friendly behavior, goodcommunication skills, physical and mental endurance, professional, creative, understanding everything about the products. (2) Performance of an SPG, namely how to make the consumers sympathize, findcommon interests and hobbies, become a helping angel and a good listener in order to find a solution for consumers, and customer service for a positive impression on consumers. (3) Neat appearance, thick makeup, tight clothes, different perfumes every day, other supports are iPhone mobile phones, alexandercristie watches, Rolex, 4-wheeled vehicles as appearance support, (4) backstage spg, rarely socialize withthe community, introvert, prefers to be lazy, dressing as is, when at home wearing a negligee and no makeup. It can be seen that the self-presenting done by PT Toyota's car sales promotion girls shows a difference when in front of the stage and backstage. When in front of the stage, the SPGs are very concerned about their performance and appearance as a form of the self-image of an SPG who is friendly, warm, and beautiful. Whereas it is very different when they are backstage when they are not working, the SPGs are more closed so that they rarely socialize with the community, are lazy to do activitiesoutside/inside the house, do not pay attention to their appearance, and do not wear makeup.